Altered Immunoregulation in Rheumatoid Arthritis: The Role of Regulatory T Cells and Proinflammatory Th17 Cells and Therapeutic Implications - Alessia Alunno; Mirko Manetti; Sara Caterbi; Lidia Ibba-Manneschi; Onelia Bistoni; Elena Bartoloni; Valentina Valentini; Riccardo Terenzi; Roberto Gerli (Mediators of Inflammation)
In recent years several studies investigated the role of T lymphocyte subpopulations in the pathogenesis of rheumatoid arthritis (RA). Pathogenic Th17 cells mediate pannus growth, osteoclastogenesis, and synovial neoangiogenesis; hence they are key players in the development of the disease. On the other hand, regulatory T (Treg) cells are a T cell subset whose peculiar function is to suppress autoreactive lymphocytes. The imbalance between Th17 and Treg cells has been identified as a crucial event in the pathogenesis of RA. In addition, the effects of currently employed RA therapeutic strategies on these lymphocyte subpopulations have been extensively investigated. This review article aims to discuss current knowledge on Treg and Th17 cells in RA and possible implications of their therapeutic targeting in this disorder.